Selection of Local Microorganism Solutions as Crude Fiber Digester in Areca catechu L. Peel Waste for Producing Poultry Feed Additives - Mahata , Maria Endo; Ardi,; Rizal, Yose (International Journal of Poultry Science, 2019)
Background and Objective: Areca catechu L. is an herbal plant that contains polyphenol (flavonoids and tannin) and alkaloid (arecholine, arecolidine, guvacoline, guvacine and isoguvacine) compounds. Both polyphenols and alkaloids are known to be anthelmintic as well as antibacterial, antifungal, anti-inflammatory, antioxidant and cholesterol lowering compounds for poultry and dogs. When Areca catechu L. seeds are harvested, they produce 76% Areca catechu L. peel waste, which can be potentially used as a poultry feed additive to increase poultry performance. Areca catechu L. peel waste contains as much as 1.693% total polyphenols, 1.383% total alkaloids, 1.466% catechins and 456.59 mg/100 g tannins. The utilization of Areca catechu L. peel waste as a poultry feed additive is limited due to the high crude fiber content, which can be as high as 47.02%; the poultry digestive tract does not produce cellulase to hydrolyze crude fiber. The fermentation of Areca catechu peel waste with a local microorganism solution that produces cellulase is one solution for lowering crude fiber in Areca catechu L. peel waste. This experiment was performed to select the best local microorganism solution from different sources as a crude fiber digester in Areca catechu peel waste to produce poultry feed additives. Materials and Methods: This experiment was performed with a completely randomized design using five different sources of local microorganism solutions derived from bamboo sprouts, banana corms, mixed fruit waste, mixed vegetable waste and rice waste. As much as 500 mL of each local microorganism solution was used to ferment 200 g of Areca catechu L. peel waste for 2 weeks and each treatment was repeated four times. Crude fiber and dry matter were the parameters in this experiment and the total number of colonies of bacteria and fungi was calculated before and after fermentation with each local microorganism solution. Results: The fermentation of Areca catechu L. peel waste with different sources of local microorganism solutions significantly lowered crude fiber and dry matter (p